Health literacy in low‑ and middle‑income countries: What is the evidence for noncommunicable diseases? - AZA-GNANDJI, Guy-Gérard (My University, 2023)
Health literacy (HL) is defined as a person’s ability to access, understand, appraise, and apply health information in order to make sound health decisions. It has emerged as a key determinant of health outcomes, more particularly in noncommunicable diseases (NCDs). Low HL has been associated with lower use of health‑care services and poorer health outcomes, including increased morbidity and mortality. During the second meeting of the EMAC‑AOC Group (Epidemiology of Chronic Diseases – Central and Western Africa), HL and NCDs in low‑ and middle‑income countries (LMICs) were discussed to explore options for interventional studies in sub‑Saharan Africa on NCDs’ prevention and control. We reviewed how HL is defined, how it is associated with health outcomes and health inequities, and what instruments are available to assess it. Several published studies, systematic reviews, especially in LMICs, as well as national and international recommendations were discussed to explore potential approaches to improve HL in a study evaluating interventions for the prevention and control of NCDs in Africa.
Keywords: Health literacy; low‑ and middle‑income countries; noncommunicable diseases